An Empirical Analysis of Vulnerability to Poverty in Nigeria: Do Household and Regional Characteristics Matter? - Mba, Peter N.; Nwosu, Emmanuel O.; Orji, Anthony (International Journal of Economics and Financial Issues, 2018)
This paper investigates vulnerability to poverty in Nigeria using the revised General Household Post-harvest survey for Nigeria 2010. The results show that female-headed households, living in rural area and large household size have significant positive impact on household vulnerability. Again, compared to household heads aged between 15-24 years, vulnerability significantly decreases as age range increases. However, the rate of decrease is higher among the segment of the population in the active labour force. That is, those between 25 and 54 years. The rate of decrease in vulnerability is marginal in all other northern zones relative to north east but large in the southern geopolitical zones. We therefore conclude that extension of government sponsored or support programmes to female headed households may be helpful to protect them, especially for widows in reducing their vulnerability. Youth’s involvement in entrepreneurship, skills acquisition and agriculture through proper funding of the sector will be helpful in reducing their vulnerability and make them self-reliance. Keywords: Empirical, Analysis, Vulnerability; poverty JEL Classifications: I32, D10